William Faulkner : an economy of complex words - Godden, Richard, 1946- (20/21 (Princeton, N.J.), 2007)
In William Faulkner, Richard Godden traces how the novelist's late fiction echoes the economic and racial traumas of the South's delayed modernization in the mid-twentieth century. As the New Deal rapidly accelerated the long-term shift from tenant farming to modern agriculture, many African Americans were driven from the land and forced to migrate north. At the same time, white landowners exchanged dependency on black labor for dependency on northern capital. Combining close readings of The Hamlet, Go Down, Moses, and A Fable with an examination of southern economic history from the 1930s to the 1950s, Godden shows how the novels' literary complexities--from their narrative structures down to their smallest verbal emphases--reflect and refract the period's economic complexities. By demonstrating the interrelation of literary forms and economic systems, the book describes, in effect, the poetics of an economy. --From publisher's description.